2002
DOI: 10.1093/nar/gkf557
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network prediction of antisense oligodeoxynucleotide activity

Abstract: An mRNA transcript contains many potential antisense oligodeoxynucleotide target sites. Identification of the most efficacious targets remains an important and challenging problem. Building on separate work that revealed a strong correlation between the inclusion of short sequence motifs and the activity level of an oligo, we have developed a predictive artificial neural network system for mapping tetranucleotide motif content to antisense oligo activity. Trained for high-specificity prediction, the system has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Among all 9 variations considered in Table 1, the best performance (ROC = 0.973) was achieved when the GS and Triplet profiling are used in conjunction on mRNA. This performance is apparently better than that of the previous methods on the same data set [5,6]. Profiling on parenthesis orientation sensitive triplets and quadruplets was also tested, but did not improve the performance, instead the performance decreased slightly (results not reported here).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Among all 9 variations considered in Table 1, the best performance (ROC = 0.973) was achieved when the GS and Triplet profiling are used in conjunction on mRNA. This performance is apparently better than that of the previous methods on the same data set [5,6]. Profiling on parenthesis orientation sensitive triplets and quadruplets was also tested, but did not improve the performance, instead the performance decreased slightly (results not reported here).…”
Section: Resultsmentioning
confidence: 68%
“…Several computational methods have thus been developed to this end [3,4,5,6]. Essentially, these methods rely on various sequential and structural features to differentiate antisense oligonucleotides with high efficacy from those with low efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been much interest in computational approaches to the to the secondary stuctures prediction of mRNA have advantages over experimental methods in terms of throughput, cost, and efficiency. Some approaches to efficacy prediction have been proposed for rational selection of target sites [29][30][31][32]. Thierry et al [33] indicated that single-stranded loop regions in mRNA secondary structure were the best target sites for accessibility of antisense reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Another method is to look for motifs that occur more often in effective AOs. Ten sequence motifs have been identified with a correlation to AO efficacy in [20], and recently, motifs have been used as the input to neural network models [21,22] with reasonable success.…”
Section: Introductionmentioning
confidence: 99%